The Impact of Watching Movies on Enhancing Spoken English - Omer Mohamed Taha Alkanan; Nelia Fariani; M Septian Arya Permana; Muhammad Irvan; Farhatul Azizah, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study aims to explore the impact of watching movies on enhancing spoken English skills. The method used in this research was a quantitative approach, involving the distribution of online questionnaires to 78 respondents from various age groups, educational levels, and professional backgrounds. Data collection was conducted within one day, and the analysis involved classification and tabulation to address the research questions. The results reveal that spoken English remains essential in both social and professional settings. However, learners face several obstacles, such as difficulties in grammar, pronunciation, vocabulary, and lack of confidence. Movies were identified as the most comfortable and accessible medium for learning spoken English. Watching movies positively impacts spoken English skills, particularly in mastering pronunciation, accent, vocabulary, and conversation comprehension. This study recommends movies as an effective and enjoyable medium to improve spoken English skill.